2009
DOI: 10.1159/000229765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Hormone Treatment on Growth in Children with Juvenile Idiopathic Arthritis

Abstract: Background: Several therapeutic trials have been conducted over the past decade to evaluate the role of exogenous growth hormone (GH) as a means of correcting the growth deficiency seen in children with juvenile idiopathic arthritis (JIA). Early studies showed the benefit of GH treatment with respect to final height in patients with JIA. Of 13 patients receiving GH, 84% (11 patients) achieved a final height within their target range compared with only 22% (4 of 18 patients) of untreated patients. There are, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
0
15
0
10
Order By: Relevance
“…Whereas disease activity and the dose of prednisolone have a negative effect, the dose of rhGH has a positive effect on the growth response [60] . Although no adverse effects were observed in these patients, transient glucose intolerance with rhGH reported in a previous study highlights the need to evaluate safety long-term [59] .…”
Section: Crohn's Diseasementioning
confidence: 64%
See 2 more Smart Citations
“…Whereas disease activity and the dose of prednisolone have a negative effect, the dose of rhGH has a positive effect on the growth response [60] . Although no adverse effects were observed in these patients, transient glucose intolerance with rhGH reported in a previous study highlights the need to evaluate safety long-term [59] .…”
Section: Crohn's Diseasementioning
confidence: 64%
“…Trials of rhGH in selected children with persistently active JIA and severe growth failure have reported improvements in linear growth after 6 months of treatment [58] as well as a sustained effect for up to 4 years [59,60] . Intervening with rhGH earlier on in the course of the disease is speculated to minimize the significant loss in height, especially in patients treated with corticosteroids [59] .…”
Section: Crohn's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, combined therapy of rhGH and rhIGF-I counteracted selected negative effects of glucocorticoids on bone in healthy volunteers who received short-term glucocorticoid therapy (29). Observational and controlled studies in children receiving glucocorticoid therapy for juvenile idiopathic arthritis showed that rhGH restored normal height velocity with a concomitant improvement of bone mineralization (30)(31)(32)(33). However, the efficacy of rhGH and rhIGF-I treatment in GIO is controversial and needs to be documented by welldesigned prospective controlled studies.…”
Section: Extraskeletal Effects Of Glucocorticoids On Bone Metabolismmentioning
confidence: 99%
“…Low dose treatment involves linear growth mainly in pediatric asthmatic cases. Corticosteroids can inhibit mechanisms and organ responsiveness therefore the use of recombinant growth hormones could rehabilitate growth velocity 36 . Furthermore, steroid myopathy is eventuated by high dose corticosteroid treatment combined with sedentary lifestyle.…”
Section: The Effects Of Anabolic Steroids On the Musculoskeletal Systemmentioning
confidence: 99%